Treatment patterns in advanced melanoma: findings from a survey of European oncologists. (18th May 2015) - Jones, C.; Zhao, Z.; Barber, B.; Bagijn, M.; Corrie, P.; Saltman, D.
<x xml:space="preserve">Abstract</x> With the emergence of new therapies, established patterns of treating advanced melanoma are changing. The aim of this study was to understand how advanced melanoma is treated in clinical practice in Europe following the introduction of ipilimumab and vemurafenib. An online survey was conducted between August and November 2012 with 150 oncologists and dermatologists, from France, Germany, Italy, Spain and the UK; respondents reported treating the majority of patients with one or two lines of therapy. For BRAF mutant melanoma, the most frequently used first‐line treatments were vemurafenib and dacarbazine. For BRAF wild‐type melanoma, the most frequently used first‐line treatment was dacarbazine. There was no single preferred agent for the second‐line treatment of BRAF mutant or BRAF wild‐type disease. Most sequencing from first‐ to second‐line was from conventional dacarbazine to newer agents such as ipilimumab and vemurafenib. The treatment of advanced melanoma is rapidly evolving due to the introduction of new agents. This study presents an early insight into access to the new agents, ipilimumab and vemurafenib, and clinical practice in several European countries.